On the Modern Teacher’s Job Specification: Results of a Representative Survey of School Directors - Merkys, Gediminas; Čiučiulkienė, Nijolė; Bubelienė, Daiva (Pedagogika, 2023)
The article reveals the importance of non-cognitive personality characteristics (NPC) for the successful professional activities of teachers. In the modern teacher training system, the role of the NPC is not estimated enough, the modern models of school and university socialization do not contribute to the successful formation of the NPC. The theoretical discussion of this research paper is based on the results of the mass survey (N = 929) of school principals’ attitudes on NPC. The findings show that school leaders recognize the importance of the NPC for professional success.